Karakteristik Morfologi dan Analisis Fenetik Kerbau (Bubalus bubalis) Nusa Tenggara Barat - Akhmad Sukri (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Measurement of morphological characteristics is needed to understand buffalo's conformation, productivity and reproduction. This study aims to describe the morphological characteristics of buffalo taken from the West Nusa Tenggara region and to carry out phenetic analysis based on the results of morphological character measurements. This study was exploratory with 16 individual buffalo as subjects taken purposively from two different populations, namely West Sumbawa and West Lombok Regencies, West Nusa Tenggara. The morphological characters measured included leg length, hip width and head width. Morphological character data were analyzed descriptively and non-parametrically using the Mann-Whitney test. In contrast,the phenetic analysis used the Unweighted Pair Group Mean Average (UPGMA) method supplemented by Principle Component Analysis (PCA). The measurement results showed variations in the morphology of the buffalo (Bubalus bubalis) in West Sumbawa and West Lombok Regencies. The character of leg length was significantly different in both populations (Sig <.05). In contrast, the other two characters, namely head width and hip height, were not significantly different (Sig >.05). Furthermore, the phenetic analysis showed that the relationship between the two populations of buffalo was significantly different, which was strengthened through PCA analysis which revealed that there was no genetic mixing between the buffalo populations.